Reuse of building materials—the perspective of Swedish clients - Filip Ericsson; Kristina Mjörnell; Ulla Janson (Cleaner Engineering and Technology)
In the context of the circular economy, there is an urgent need for transformation into circular material flows by avoiding waste, reducing extraction of virgin raw materials, and extending product life cycles. Within the construction and real estate industry, the reuse of building materials stands out as a critical strategy for value retention. The objective of this paper is to localise the forefront of the practical implementation of reused materials within the Swedish construction and real estate industry. To achieve this, the current state of reuse practices through the perspective of property companies as clients in decision-making positions was conducted through semi-structured interviews to identify key barriers and enablers associated with reuse. The three most significant barriers that emerged were a lack of measurable economic incentives, the absence of a professional reuse market, and obsolete project management. Conversely, the three most significant enablers were new and improved project management methods, enhancing competence and learning within and beyond organisations, and introduce reuse at an early stage. The results emphasise the need for project management to develop and adopt circular economy principles. This is further understood due to responders highlighting the industry's linear approach as a major obstacle to circularity together with uncertainties related to product performance, responsibilities and economics characterising reuse efforts. However, an industry in transition is witnessed, e.g. by the emergence of new roles which suggests a continued need for focused research in organisational matters.